2020
DOI: 10.1002/brb3.1639
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of white matter integrity associated with cognitive deficits in patients with glioma

Abstract: Objective This study aimed to investigate the characteristic of brain structural connections in glioma patients and further evaluate the relationship between changes in the white matter tracts and cognitive decline. Methods This retrospective study included a total of 35 subjects with glioma and 14 demographically matched healthy controls, who underwent diffusion tensor imaging scans and formal neuropsychological assessment tests. Fractional anisotropy (FA) values of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 56 publications
2
23
0
Order By: Relevance
“…This insult of the structural connectivity is correlated with a decline of cognitive functions, confirming that axonal bundles represent a major limitation of neuroplasticity. For example, invasion of the right superior longitudinal fasciculus is correlated to a visuo-spatial deficit [ 37 ], invasion of the left inferior fronto-occipital fasciculus to a semantic deficit [ 38 ], or invasion of the right cingulate to a mentalization deficit [ 39 ]. This low potential of structural reconfiguration and rewiring within the function-specific WM pathways [ 40 ] may indirectly participate in the compensatory changes of the intra- and inter-system functional connectivity at the level of the whole meta-networking brain.…”
Section: The Contribution Of Fni and Tms Mapping To Investigate Inmentioning
confidence: 99%
“…This insult of the structural connectivity is correlated with a decline of cognitive functions, confirming that axonal bundles represent a major limitation of neuroplasticity. For example, invasion of the right superior longitudinal fasciculus is correlated to a visuo-spatial deficit [ 37 ], invasion of the left inferior fronto-occipital fasciculus to a semantic deficit [ 38 ], or invasion of the right cingulate to a mentalization deficit [ 39 ]. This low potential of structural reconfiguration and rewiring within the function-specific WM pathways [ 40 ] may indirectly participate in the compensatory changes of the intra- and inter-system functional connectivity at the level of the whole meta-networking brain.…”
Section: The Contribution Of Fni and Tms Mapping To Investigate Inmentioning
confidence: 99%
“…Typically, LGG patients with involvement of the left IFOF may exhibit a decline of semantic fluency at diagnosis ( 78 ) ( Figure 1A ). Using each patients’ DTI, reduced fractional anisotropy values in the right superior longitudinal fasciculus (SLF) affected by the glioma were associated to visuospatial impairments ( 82 ).…”
Section: Wm Tracts As a Main Limitation Of Neuroplasticity: Functiona...mentioning
confidence: 99%
“…An example of AF asymmetry in one patient treated at our hospital can be seen in Figure 1 , whereas Table 1 reports the main studies including AF tractography for surgical planning on patients with gliomas. Only few of them took into account contralesional WM bundles ( 19 , 69 , 70 ). In 2018, Jehna et al demonstrated that, at presentation, language functions were worse in patients in whom the AF was left-lateralized, whereas patients with symmetric or right-lateralized AF reconstructions showed better language performance ( 19 ).…”
Section: Lateralization Of Arcuate Fasciculus In Relation To Hemisphementioning
confidence: 99%